2017
DOI: 10.1002/2017sw001637
|View full text |Cite
|
Sign up to set email alerts
|

Linear forecasting of the F10.7 proxy for solar activity

Abstract: The ability to accurately forecast variations in the solar extreme ultraviolet irradiance is important to many aspects of operational space weather. For example, variations in the Sun's radiative output at these wavelengths drive changes in thermospheric density, which perturbs the trajectories of objects in low Earth orbit. Thus, predicting the conjunction of an operational satellite with orbital debris requires accurate forecasts of solar activity. In this paper we present a simple linear forecasting model f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…But to be considered for operational deployment, the forecast accuracy of these approaches needs to be tested against the performance of the current operational inputs, such as F 10.7 or other proxies. For example, Warren et al (2017) find that the Henney et al (2012) method performs at a similar level to the (much simpler) F 10.7 linear forecast. As our knowledge on the evolution of solar magnetic fields improves so will such models.…”
Section: 1002/2017sw001725mentioning
confidence: 92%
See 1 more Smart Citation
“…But to be considered for operational deployment, the forecast accuracy of these approaches needs to be tested against the performance of the current operational inputs, such as F 10.7 or other proxies. For example, Warren et al (2017) find that the Henney et al (2012) method performs at a similar level to the (much simpler) F 10.7 linear forecast. As our knowledge on the evolution of solar magnetic fields improves so will such models.…”
Section: 1002/2017sw001725mentioning
confidence: 92%
“…The extrapolations are generally within the 5% density uncertainty requirement (section 2.1) for 2-3 day forecasts (Figure 3j in Emmert et al, 2017), but the 10 day EUV forecasts behave as Brownian motion and hence lead to~(time) 5 increases for in-track errors. More recently, Warren et al (2017) evaluated the performance of a linear extrapolation model for F 10.7 and showed that the forecast skill peaks at 6 days compared to climatology and persistence.…”
Section: Forecast Accuracymentioning
confidence: 99%
“…The closer to 1, the better (n∈ [ 1,29] ) days. The input signals are forwarded in the order of the input layer, the hidden layer, and the output layer.…”
Section: Bp Algorithm Bpnn Is a Multilayer Feedforwardmentioning
confidence: 99%
“…Fortunately, fully physics-based models (Richmond et al, 1992;Roble and Ridley, 1994;Millward et al, 1996;Huba et al, 2000;Ridley et al, 2006) are able to accept such drivers as input and thus can in principle be used for a-few-day lead time forecasts as long as forecasted solar drivers are available. While this research area is still in its early stages, solar wind and solar irradiance forecasts are major focuses of the space weather research effort (Owens et al, 2008;Jian et al, 2015;Henney et al, 2015;Warren et al, 2017). Therefore, we investigate thermospheric-ionospheric forecasts with a lead time of a few days from the perspective that reliable solar forecasts will eventually be available a few days ahead.…”
Section: Introductionmentioning
confidence: 99%